2020
DOI: 10.1002/ett.3940
|View full text |Cite
|
Sign up to set email alerts
|

Network video summarization based on key frame extraction via superpixel segmentation

Abstract: The spread of insecure online video has been a serious social problem. The video summarization becomes one of key step for automatic filtering the expected video from the Internet. At present, the most existing video summarization methods are based on calculating the image similarity between video frames, so that the key frame can be selected properly. In this article, we introduce a superpixel segmentation based image similarity calculation, and then the metric is applied into video summarization. To identify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…A precision of 36.6% is obtained utilizing this approach, which can be utilized for changing the yield of different procedures. A calculation that uses super-pixels for video once-over can be seen from the study [12], here, every pixel is changed over into super-pixel through similarity evaluation. This closeness respect permits the pixels to be tended to regarding each other; and starting there on by utilizing a district blending calculation; the pixels are cemented to diagram a super-pixel.…”
Section: Literature Review Deep Learning-based Video Summarizationmentioning
confidence: 99%
“…A precision of 36.6% is obtained utilizing this approach, which can be utilized for changing the yield of different procedures. A calculation that uses super-pixels for video once-over can be seen from the study [12], here, every pixel is changed over into super-pixel through similarity evaluation. This closeness respect permits the pixels to be tended to regarding each other; and starting there on by utilizing a district blending calculation; the pixels are cemented to diagram a super-pixel.…”
Section: Literature Review Deep Learning-based Video Summarizationmentioning
confidence: 99%
“…China unfortunately has a significantly aged society. With the increase in the number of elderly people herein referred to as seniors, health monitoring for seniors has become a research hotspot 1‐6 . As bodily functions age, seniors are very likely to physically fall in their daily activities.…”
Section: Introductionmentioning
confidence: 99%
“…With the increase in the number of elderly people herein referred to as seniors, health monitoring for seniors has become a research hotspot. [1][2][3][4][5][6] As bodily functions age, seniors are very likely to physically fall in their daily activities. Studies have shown that among many daily behaviors that endanger the health of seniors, sudden abnormal behaviors (such as falling) are the most harmful when they are home alone.…”
Section: Introductionmentioning
confidence: 99%